Bezold’s abscess: a rare complication of acute otitis media - Nasir, Fauziah; Asha'ari, Zamzil Amin (Academy of Family Physicians of Malaysia, 2017)
Otitis media is a common disease encountered in the primary practice. Most cases are successfully treated with antibiotics without any sequelae. Because of these, potential serious complications of otitis media may be overlooked. We report a rare case of Bezold’s abscess, as a complication of otitis media and discuss its pathophysiology and management.